2020
DOI: 10.1111/pace.14134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non‐response to cardiac resynchronization therapy by post‐procedural computed tomography

Abstract: Introduction Causes of non‐response to cardiac resynchronization therapy (CRT) include mechanical dyssynchrony, myocardial scar, and suboptimal left ventricular (LV) lead location. We aimed to assess the utility of Late Iodine Enhancement Computed Tomography (LIE‐CT) with image subtraction in characterizing CRT non‐response. Methods CRT response was defined as a decrease in LV end‐systolic volume > 15% at 6 months. LIE‐CT was performed after 6 months, and analyzed global and segmental dyssynchrony, myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The location of scar in the posterolateral region of the LV, which is empirically thought to be a target site for LV lead implantation, was associated with lower response rates following CRT (Chalil et al, 2007). In study by Pezel et al (2021), no difference was found in presence and extent of scar between CRT responders and non-responders. However, in non-responders, the LV lead was more often over an akinetic/dyskinetic area suggesting the presence of tissue lesions, a fibrotic area, or an area with myocardial thickness < 6 mm.…”
Section: Feature Selection For Classification Models From Hybrid Datamentioning
confidence: 88%
“…The location of scar in the posterolateral region of the LV, which is empirically thought to be a target site for LV lead implantation, was associated with lower response rates following CRT (Chalil et al, 2007). In study by Pezel et al (2021), no difference was found in presence and extent of scar between CRT responders and non-responders. However, in non-responders, the LV lead was more often over an akinetic/dyskinetic area suggesting the presence of tissue lesions, a fibrotic area, or an area with myocardial thickness < 6 mm.…”
Section: Feature Selection For Classification Models From Hybrid Datamentioning
confidence: 88%
“…However, there continues to exist a group of patients for whom the indication for CRT is controversial (i.e., RBBB), and approximately one third of patients with an indication for CRT have a suboptimal clinical response (i.e., "non-responders") [76]. Causes of non-response include mechanical dyssynchrony, presence and extent of myocardial scar, and suboptimal LV lead position [77][78][79]. Other factors that have been shown to influence response to CRT include QRS width and morphology pattern, device optimization, and post-implant programming [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Greater segmental dyssynchrony between the anterior and inferior segments, between the inferoseptal and anterolateral segments, and between the anteroseptal and inferolateral segments was found between non-responders. In addition, in the non-responders, the LV lead location was less often concordant with the region of maximal wall thickness (9% vs. 72%, p = .001) [78].…”
Section: Cardiac Resynchronization Therapy Guided By Computed Tomographymentioning
confidence: 91%
“…Late iodine enhancement computed tomography (LIE-CT) was found to be an important elegant diagnostic modality in this regard. Théo Pezel et al investigated CT dyssynchrony measurements for which the LV short-axis images from the multiphase reformatted reconstructions were used [78]. CT dyssynchrony indices used in their investigation were: global and segmental time to maximal wall thickness, global and segmental time to maximal inward wall motion, and time to minimum systolic volume.…”
Section: Cardiac Resynchronization Therapy Guided By Computed Tomographymentioning
confidence: 99%